The Correlation of Stress Level and Hypertension in Student of Nutrition Departmen of UIN Sunan Ampel Surabaya - Puspitasari, Devita Catur; Widayanti, Linda Prasetyaning; Suprayogi, Dedy (International Conference on Sustainable Health Promotion, 2025)
One non-communicable disease that has grown to be a major cause of death and a global health concern is hypertension. This study aims to determine the relationship between stress levels and the incidence of hypertension among third- and fifth-semester students in the Nutrition Study Program, Faculty of Psychology and Health, UIN Sunan Ampel Surabaya. Simple random sampling was used to select 85 students for this quantitative investigation. Systolic and diastolic blood pressure readings as well as a stress level questionnaire were used to gather data. According to the findings, the majority of the respondents had high systolic and diastolic blood pressure (63.5% and 60.0%, respectively) and significant stress (81.2%). Statistical analysis using the phi coefficient found a significant relationship between stress levels and systolic (p=0.008) and diastolic (p=0.041) blood pressure. Stress triggers an increase in adrenaline hormones, which raises blood pressure, so effective stress management is necessary to prevent hypertension in students.